The Pendidikan Agama Kristen Remaja Dan Aktualisasi Diri Menurut Abraham Maslow Terhadap Pembangunan Mental Remaja di Era Society 5.0 - Simatupang, Jhonnedy Kolang Nauli; Sinaga, Rut Yesika (Jurnal Apokalupsis, 2024)
In the era of Society 5.0, where human and technological collaboration is increasingly intertwined to drive social progress, the effects on human life, particularly adolescents, have been profound. Adolescents, who are in a crucial transitional phase from childhood to adulthood, are naturally curious and vulnerable to both the positive and negative influences of this digital age. This research seeks to explore how Christian Religious Education and Abraham Maslow's concept of self-actualization impact the mental development of adolescents, as an effort to mitigate the negative effects of Society 5.0. Using a descriptive qualitative approach, this study draws from a range of literature, including e-books, e-journals, and other relevant sources on Christian Religious Education, self-actualization, and mental development. The findings of this research indicate that during this period of heightened curiosity and instability, adolescents are capable of discerning the teachings that should guide their lives and realizing their full potential. Christian Religious Education plays a significant role in fostering mental health among adolescents, while self-actualization is equally critical in helping them maintain mental well-being as they navigate the challenges of Society 5.0.